Os filtros de Graham e a formação de carteiras de ações: uma proposta de adaptação ao mercado brasileiro - Barros, Mariângela Araújo (2021)
The study aimed to evaluate efficiency and adapt the assumptions of fundamentalist analysis of Benjamin Graham in the formation of stock portfolios in the Brazilian market. Such assumptions reflect the search for companies with good fundamentals, however, that show themselves in mispricing (poorly priced), believing in the possibility of obtaining returns above the market average. For this, based on the investment in value, in addition to testing the application of Graham filters in their original form, a new methodology for asset selection was proposed, adapted based on the context of the Brazilian market. In addition, the study carried out an analysis of the possible generation of Alpha in the portfolios built. For data collection, the Thomson Reuters Eikon® database was used. To adapt the filters to the Brazilian market, the median per quarter and sector was used, in addition to the ranking methodology inspired by the strategy of Greenblatt (2007). It is understood that, when calculating the median for each sector and for each filter, a cut-off parameter that is more sensible to the context under study is obtained. In order to assess and explain the abnormal return by portfolios, this research used the five-factor asset pricing model suggested by de Fama and French (1992, 1993), Cahart (1997) and Amihud (2002). The results found reinforced the difficulty of applying Graham's original filters in the Brazilian market, even after their flexibility by the median of the indicators. The suggested adapted filters represented a strategy that obtained a return higher than the market average. The results of the ranking methodology of 10, 20 and 30 assets, showed the following behaviors: the portfolios surpassed the Ibovespa, the IBrX 100 and the Financial Treasury Bills (LFTs), with the portfolio formed by the ranking of 10 assets, the strategy obtained alpha generation. However, it is necessary to observe the risks that investors took to obtain these returns. In general, the results demonstrated that it is possible to obtain abnormal returns in Brazil, but they bring to light the high volatility of the strategy in the country and the high monthly return of the asset considered risk-free in Brazil (the LFTs). Thus, the study contributes bringing a result that is consistent with the practical reality of an investor, using the rebalancing on a quarterly basis and proposing an adaptation of Graham's strategy that would be more aligned to the context of companies with shares in B3, differentiating themselves thus, from previous research that did not pay attention to such questions. Therefore, market participants will be able to use the results to support their investment decisions.